Molecular Docking Analysis of Family Fabaceae Phytochemistry to Estrogen Receptor Alpha Compared to Tamoxifen in Breast Cancer - Putra, Ega Caesaria Pratama; Pesik, Riza Novierta; Kusumawati, Ratna (Nexus Kedokteran Translasional, 2015)
Background: Breast cancer is the second most common cancer.Estrogen is the risk factor of breast cancer. Estrogen receptor Î± is expressed by 50-80% of breast cancer.Â  The mechanism of estrogen is mediated by estrogen receptor Î± and estrogen receptor Î². Tamoxifen is a selective estrogen receptor modulators (SERMs) that can be bound to the estrogen receptor Î±, therefore prevent bonding between estrogen and estrogen receptor Î±. Methods: This research used molecular docking analysis of family Fabaceaeâs Phytochemistry as an inhibitor of estrogen receptor Î± activation. This study was observational bioinformatics study to observe interaction between family Fabaceaeâs phytochemistry and estrogen receptorÎ±. Molecular docking analysis observed binding energy and binding location. This virtual screening analysis was done using PyRx, AutoDock Vina, PyMOL, Open Babel, and UCSF Chimera. Results: We obtained 471 Family Fabaceaeâs phytochemistry from database, only five compounds that have equal or lower binding energy compared with tamoxifen, that compound werebeta-amyrine (9.6 KJ/Mol), obovatin( 9.6 KJ/Mol), erythrabyssin II (9.6 KJ/Mol), Cajaflavanone (10.2 KJ/Mol), and tomentosanol E (10.5 KJ/Mol). The visualization of binding location analysis showed that only cajaflavanone which have relatively similar binding site location with tamoxifen. Conclusions: Cajaflavanone have a similar characteristic with tamoxifen, and have a potency to be used as partial antagonist of estrogen receptor alpha in breast cancer based molecular docking analysis. However, In vitro and In vivo researchneeded to determine the effectiveness. Keywords: Breast Cancer, Molecular Docking, Fabacea, Tamoxifen, Estrogen Receptor Î±Â